AMAZONE INDONESIA: UNDERSTANDING HYPERREALITY IN A FAMILY ENTERTAINMENT ARENA - Tangguh Okta Wibowo; Khairul Syafuddin (Publikasi Indonesia, 2023)
Amazone Indonesia (Amazone) is the largest family entertainment destination in Indonesia, with a large area and a complete selection of games. This article explores how myths about the Amazon forest in Brazil are managed in the form of a modern family playground in a mall, Aeon. This paper examines how Amazone exploits the myth that the Amazon forest was constructed with technology as a family playground with the intended purpose. This study uses Roland Barthes' semiotic method to look at myths that are built through technology and presented in various forms of entertainment vehicles and games in Amazone. By using Baudrillard's theory of hyperreality, this paper tries to critically examine how Amazone uses the myth of the forest to